Penerapan Metode Kepadatan Mutlak Untuk Perencanaan Campuran Beraspal Hot Rolled Asphalt - Perpustakaan UGM, i-lib ([Yogyakarta] : Lembaga Penelitian UGM, 2002)
ABSTRAK Heavy vehicles possible cause failure of road like as rutting. Their mechanism by means of secondary compaction that push asphalt to fill voids in the mixtures (VIM). If VIM less than 3 %, asphalt mixture could not compact again so asphalt would flow up and rise weak spot at road surface. Movement of vehicles would remain wheel path on road surface and then would accumulate continuously to shape rutting. The risk of rutting is more easily can be observed on the asphalt mixture containing with high asphalt content like Hot Rolled Asphalt (HRA). One of ways to reduce rutting risk is applied the refusal density methods to design asphalt mixture. This methode tries to simulate traffic compaction on asphalt mixture and control VIM so never less than 3 %. The application of the refusal density method for design HRA resulted in the optimum bitumen content (OBC) of 9.25 %. A group of samples that was made at OBC had an average of Voids in the Mineral Aggregates (23.08 %), Voids In the Mixtures (4.78 %), Voids Filled with Asphalt (79.30 %), stability (1278 kgs), flow (3.93 mms), Marshall quotient (325 kes/inin) dan retained stability (95.17 %). These results show that the asphalt mixture satisfied requirements of criteria according to the Draft of Indonesian National Standard Specification of Hot Mixed Asphalt (1998). Keywords: Metode kepadatan, aspal hot rolled asphalt